MANAJEMEN SUMBER DAYA MANUSIA DI UD KUDA MASS DALAM MENINGKATKAN KINERJA KARYAWAN - M. Zikwan; A. Muhyiddin Khotib (Al-Idarah, 2020)
Human Resources is one of the resources contained in the organization, including all people who carry out activities. In general, the resources contained in the organization can be grouped into two types, Human Resources, Resources. Included in this non-human resource group include capital, machinery, technology, materials. UD Kuda Mass Turen Malang is a UD which operates in the Macaroni sector, in its role as one of the driving wheels of the economy in the village of Reject Turen Malang UD Kuda mass was exposed to UD who maintained Islamic ethics, in the sense that UD Kuda Mass did not only work for the world alone. however, the application of the responsibility of a Muslim is also carried out at the UD. In his duties as an entrepreneur that combines the world and the hereafter.